How Advanced are Cancer Immuno-Nanotherapeutics? A Comprehensive Review of the Literature - Yadav D; Puranik N; Meshram A; Chavda V; Lee PCW; Jin JO (International Journal of Nanomedicine, 2023)
Dhananjay Yadav,1,* Nidhi Puranik,2,* Anju Meshram,3,* Vishal Chavda,4 Peter Chang-Whan Lee,5 Jun-O Jin6 1Department of Life Science, Yeungnam University, Gyeongsan, 38541, South Korea; 2Biological Sciences Department, Bharathiar University, Coimbatore, Tamil Nadu, 641046, India; 3Department of Biotechnology, Kalinga University, Naya Raipur, Chhattisgarh, India; 4Department of Pathology, Stanford School of Medicine, Stanford University Medical Center, Stanford, CA, 94305, USA; 5Department of Biomedical Sciences, University of Ulsan College of Medicine, Asan Medical Center, Seoul, 05505, South Korea; 6Department of Microbiology, University of Ulsan College of Medicine, Seoul, 05505, South Korea*These authors contributed equally to this workCorrespondence: Peter Chang-Whan Lee, Department of Biomedical Sciences, University of Ulsan College of Medicine, Asan Medical Center, Seoul, 05505, South Korea, Email pclee@amc.seoul.kr Jun-O Jin, Department of Microbiology, University of Ulsan College of Medicine, Seoul, 05505, South Korea, Email junojin@amc.seoul.krAbstract: Cancer is a broad term for a group of diseases involving uncontrolled cell growth and proliferation. There is no cure for cancer despite recent significant improvements in screening, treatment, and prevention approaches. Among the available treatments, immunotherapy has been successful in targeting and killing cancer cells by stimulating or enhancing the body’s immune system. Antibody-based immunotherapeutic agents that block immune checkpoint proteins expressed by cancer cells have shown promising results. The rapid development of nanotechnology has contributed to improving the effectiveness and reducing the adverse effects of these anti-cancer immunotherapeutic agents. Recently, engineered nanomaterials have been the focus of many state-of-The-art approaches toward effective cancer treatment. In this review, the contribution of various nanomaterials such as polymeric nanoparticles, dendrimers, microspheres, and carbon nanomaterials in improving the efficiency of anti-cancer immunotherapy is discussed as well as nanostructures applied to combination cancer immunotherapy.Keywords: nanotechnology, combination therapy, cancer therapy, engineered nanomaterials, nanotoxicity, synergistic therapy